Low-Cost Thin Film Perovskite Solar Cells - Duarte, Eduardo Manuel Ribeiro (2018)
Perovskite is a class of materials named after their characteristic crystal structure, presenting excellent optoelectronic properties. These properties (particularly, ambipolar charge transport) allow these materials to integrate solar cells with and without the addition of selective layers, like Electron-Transport-Layer and Hole-Transport-Layer, possessing also the ability to be fabricated using simple, non-expensive, solution processing techniques, like Spin-Coating. Coupled with its facile production, the steep rise in SC efficiency over the last years, makes these materials a strong candidate to replace Silicon in the photovoltaic market, both in solid-state and flexible devices. Despite its many advantages, Perovskite SC still face considerable costs regarding processing conditions and HTL materials. By fabricating these devices under ambient air conditions and using Copper(I) Thiocyanate as the material for the HTL, the fabrication costs are significantly reduced. To further lower fabrication cost, Methylammonium Chloride is studied as a replacement for Methylammonium Iodide in Perovskite precursor solution fabrication. Using this solution, crystalline films were obtained, studying several deposition parameters, and the best reported ones, should provide a starting point for further optimization under similar fabrication conditions. The main goal for this work was the optimization of SC, using Spin-Coating technique, keeping the devices as low-cost as possible. Improving Perovskite film quality is detrimental to enhance SC performance, which is why efforts were made to minimize film degradation during Perovskite film fabrication and HTL deposition steps. Due to the hygroscopic nature of the organic component in Perovskite films, the influence of humidity levels was tested, and methods to reduce thin film degradation via humidity exposure were also evaluated. Overall, device optimization was successful, with Perovskite films reaching >95% bulk density and the champion device presenting PCE of 2.65%, with Jsc of 15.11 mA/cm2 and Voc of 0.701V.